The Effectiveness Of Teaching Writing Of Descriptive Text Using Tourism Object Video At The Tenth Grade Of SMKN 1 Geger In Academic Year 2013/2014 ( A Quasi-Experimental Research ) - Jaenuri, Jaenuri; , Agus Wijayanto, Ph.D; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This thesis depicts The Effectiveness of Teaching Writing of Descriptive Text Using Tourism Object Video at The Tenth Grade Students of SMK N 1 Geger In The Academic Year 2013/2014. The objective of the research is to depict the students' writing skill before using tourism object video in SMK Negeri 1 Geger, to elaborate the students' writing skill after using tourism object video in SMK Negeri 1 Geger, to identify the effectiveness of using tourism object video, to increase the students' writing skill in tenth grade of SMK Negeri 1 Geger, to illustrate the students' problems in writing skill using tourism object video, to depict the teacher's problems to teach writing skill to students of tenth grade of SMK Negeri 1 Geger in academic year 2013 / 2014. It is expected that the result of the research will provide a deeper understanding about using Tourism object video as a teaching media for English teachers and also for the readers. In order to obtain the objective of this study, the researcher will design a quasi - experimental using pre-test and post-test. The population of this study is the tenth grade student of SMKN 1 Geger, in the Academic Year 2013/2014. The sample of this study is Accounting 2 class the tenth grade that consists of 32 students. Before the experiment was conducted, the students were given a pre-test. At the end of the experiment, the students were given a post-test. To analyze pre-test and post-test, the researcher used t-test by using SPSS 17 program. The result of the study showed that there is an increasing of students' progress after the students were given treatment. And the students' achievement in mastering writing descriptive text was really excellent. In computation t test, alpha level used is 0.05. T table score was 2.02. Based on the score obtained, t value is greater than t table (7.34>2.02). Therefore, the researcher can conclude that the use of Tourism object video is really effective to improve students' writing ability. Founded on the result of the study, the researcher suggested that the use of tourism object video can be an alternative way to teach the language learner, especially to improve the students' writing ability. This result hopefully would motivate language teacher to use Tourism object video in teaching English as a foreign language in the classroom, especially when teaching English writing to the senior high and vocational students as well.